Pengaruh Aplikasi Metode Bom (Breastcare, Oxytocin Massage, and Marmet Technique) Terhadap Kecukupan Asi Ibu Post Partum di Rumah Sakit Al Fatah Ambon - Tahapary, Westy; Siahaya, Alisye (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2025)
Exclusive breastfeeding is crucial for infant health, but many mothers face challenges in maintaining adequate milk supply. The BOM method, combining breastcare, oxytocin massage, and Marmet technique, may help improve breastmilk production. This study aimed to assess the effect of the BOM method on breastmilk adequacy in postpartum mothers. A quasi-experimental study with one group pretest-posttest design was conducted on 30 postpartum mothers at Al Fatah Hospital Ambon. Breastmilk adequacy was assessed before and after the BOM intervention using a questionnaire and direct observation. Data were analyzed using univariate and bivariate analyses with the Wilcoxon test. All participants were aged 20-35 years. Before the intervention, 100% had inadequate breastmilk production. After applying the BOM method, 80% showed improved breastmilk adequacy, while 20% remained inadequate. The Wilcoxon test revealed a significant effect of the BOM method on breastmilk adequacy (p=0.013). The BOM method significantly improves breastmilk adequacy in postpartum mothers. This intervention can be incorporated into postpartum care programs to support successful breastfeeding. Further research with different variables is recommended to expand the evidence base.